Multi-indicators of Successful Aging in Centenarians - Araújo, Lia (2019)
Introduction: The multidimensional model of successful aging (Young, Frick & Phelan., 2009) has been serving as a reference in empirical studies of successful aging over the last years (e.g., Pruchno et al., 2010) and a benchmark to assess the health and functioning of very old individuals (Philips Lifeline, 2014). By comprising bio, psycho and social domains, it constitutes a promising approach to the study of the centenarian population who tend to present several age-related losses. Objectives: The study aims to validate a multidimensional model of successful aging in a sample of Portuguese centenarians. Methods: 80 centenarians from the PT100 project (Oporto and Beira Interior Centenarians Studies) were face-to-face interviewed. Indicators of disease and physical impairment (physiological domain), emotional vitality and inner contentment (psychological), and engaging with life and spirituality (sociological) were collected. Results: Structural equation modeling analysis to the hypothesized model suggests removing the social activities indicator (factor loading of 0.07). The alternative model ts well to the observed data, with x2(24) = 29.058, p = 0.218, CFI = 0.949, GFI = 0.925, RMSEA = 0.052, p = 0.048. Conclusions: The consideration of multi indicators of successful aging enables considering compensatory mechanisms and synergies between physical, psycho and social domains. A greater focus on psychosocial domains values the individual capacities’ of adaptation, resilience, and coping, which have been tremendously advocated in the gerontological literature (Baltes & Baltes, 1990; Jeste, Depp, & Vahia, 2010).